Praktek Berkunjung Pekerja Seks Komersial (PSK) ke Klinik IMS Puskesmas Baturaden II Kabupaten Banyumas - Suparmi Suparmi; Tinuk Istiarti; Harbandinah Pietojo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
The high rates of STIs in sex workers residing in Baturraden will also affect the high transmission of STIs to other people or service users PSK. The study aims to analyze the knowledge about IMS and attitudes about IMS factors that influence the practice of visiting prostitutes IMS Health Center Clinic Baturraden II. This research is an explanatory research methods and quantitative research with cross sectional approach. Collecting data used purposive sampling technique. Data analyzed by univariate analysis, frequency distributions, bivariate analysis with chi-square test, and mulivariat analysis with logistic regression. The results showed no relationship between the dependent variable practice of visiting the STD clinic with STI knowledge, attitudes towards STIs, attitudes toward STI and there is no relationship between the dependent variable practices of visiting the STD clinic with independent variable of STIs clinical knowledge. Multivariate analysis states that the attitude towards STIs variable is a variable that has the most dominant influence on the practice of visiting the STD clinic.